Determinants of Capital Expenditure Allocation in Central Sulawesi Province 2019–2023 - Rahmat Lasimpala; Edhi Taqwa; Yunus Sading; Suparman Suparman; Rita Yunus (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the influence of Regional Original Revenue (PAD), Special Allocation Funds (DAK), and Economic Growth on Capital Expenditures in Regency and City Governments in Central Sulawesi between 2019 and 2023. Data are drawn from Regional Revenue and Expenditure Budget (APBD) reports issued by the Directorate General of Fiscal Balance (DJPK) and publications from the Central Statistics Agency (BPS). The researchers used panel data regression to test this information.The Common Effect Model was used. This method was chosen after conducting the Chow and Lagrange Multiplier tests. Before using the model, researchers checked the classical assumptions to ensure the reliability of the analysis. The results show that PAD, DAK, and Economic Growth collectively have a strong influence on Capital Expenditure, explaining approximately 53.53% of the variation. Each of these factors also has a positive and significant influence when considered separately. These results suggest that increasing fiscal capacity by better managing PAD, using DAK effectively, and maintaining stable economic growth can help increase regional investment through capital expenditure.